Smart Mirror Based Home Automation Using Voice Command and Mobile Application - Shakir, Muhammad; Karim, Shahid; Fatima, Zaheen; Kumar, Vishal; Mehmood, Mamoon; Memon, Shahzor; Mustafa, Halar (EAI Endorsed Transactions on Scalable Information Systems, 2021)
The smart mirror helps humans to use their time effectively. It serves as the simple mirror and allows the user to see important updates and control electrical appliances simultaneously. Smart mirror is developed to let the user do multi-tasks while he was leaving from home. This system consists of two applications one is the smart mirror application developed using python and Tkinter library. The second one is smart mirror mobile application developed using the IONIC mobile development framework. Firebase firestore real-time database is exploited to show the user the latest news, weather updates, the current date, and time. It also allows the user to add his to-do list items. The user can control home appliances using voice commands and mobile applications. There is also a security module that captures the image of an intruder and sends the message to the mobile application. Smart mirror is developed to reduce human efforts and to allow the users to use their time effectively.